Cauchy G-spaces: Local convexity - Bernd Losert; Gary Richardson (Applied General Topology)
Cauchy continuous actions of a Cauchy monoid acting on a locally convex Cauchy space X are investigated. The local convexity is determined by a partial order on X. Sufficient conditions are given to ensure the existence of a Hausdorff Cauchy space completion T for which the Cauchy continuous action can be appropriately extended to T.